A Conceptual Metaphor Analysis of Reports on the Killing of a Hamas Leader, Yahya Sinwar - Ali, Dewi Hajar Rahmawati; Ariastuti, Marti Fauziah (UIN Syarif Hidayatullah Jakarta, 2025)
This study investigates the conceptual metaphors in The New York Times and Al Jazeera’s news reports on the murder of Hamas Leader, Yahya Sinwar. The reports were published in both media outlets within a month after the assassination in October 2024. This study attempts to compare the conceptual metaphors utilized in the two media outlets and to identify how they influence discourse in a manner that reveals media bias toward the opposing parties. The study maintains Lakoff and Johnson’s Conceptual Metaphor Theory and adopts the metaphor identification procedure to identify metaphorical lexical units. The collected data are further examined using Chateris-Black’s Critical Metaphor Analysis to discover the way conceptual metaphors influence discourse to convey media predisposition. The results show that both media outlets utilized three parallel target domains: THE MURDER, THE CONFLICT, and YAHYA SINWAR. However, the source domains display divergent results indicating bias, with The New York Times leaning toward supporting Israel, while Al Jazeera chooses to uphold the positive image of Yahya Sinwar. Further research could investigate the utilization of contextual metaphors across a broader selection of articles and the degree to which media outlets deliberately utilize the metaphors in their reports.